Los cementerios privados en el área metropolitana de Buenos Aires : arquitectura y paisaje como claves de diferenciación social - Cueto, Carla del (Visioni LatinoAmericane.)
This article is part of a research line on the changing cultural practices around death. In particular, we analyze the private cemeteries of Buenos Aires, their architectural and landscape trends, and the ideas about death that appear explicitly or implicitly in the ways in which they are designed, built and sold. We try to highlight the importance of the spatial analysis, since architecture and landscape have become important in relation to the differentiation of the supply of burial places, which in turn is part of broader processes of social and cultural differentiation.